Analysis of Social Mapping to Arrange the Corporate Social Responsibility Program of PT. Indocement Tunggal Prakarsa Tbk (Case Study of Ciwaringin Village) - Nurhawaeny Kardiyati, Endah; Wijaya, Mahendra; ., Suwarto; ., Supriyadi (KnE Social Sciences, 2020)
At present, the company is required to manage the impact of corporate activities to enable the creation of sustainable development. The sustainable development will certainly only be achieved if since the companies manage the impact of operations on three levels of impact: 1) economy, 2) social and 3) environment. The social mapping method or social mapping used includes Data Study, In-depth Interview, Survey, Location Search (Transect), FGD (Focus Group Discussion) and Secondary Data. Based on the results of social network mapping the strength of formal institutions in Ciwaringin Village is an institution that is legally within the authority of the Village. The role of formal institutions such as Pemdes, BPD, LPMD and MUI, PKK and Karang Taruna is very meaningful for the progress of village development. Analysis of social networks and the degree of importance of each stakeholder have the strength of each actor who is able to move the masses. Stakeholder analysis found that Pemdes were in constructive positions. Identification of social problems is a social problem such as the problem of poverty in the Ciwaringin Village. The mapping results based on FGDs can be grouped into three categories of poverty, namely the poor, the near-poor and the vulnerable groups. Besides the problem of poverty, the problem of unemployment is also a social problem. From the identification results, the average number of unemployed people in Ciwaringin Village is 0.9% in each RW in Ciwaringin Village. Besides identifying social problems, Ciwaringin Village also has social capital that can be used as a potential in overcoming problems in Ciwaringin Village such as social capital, human capital, physical capital, natural capital, and financial capital. The average social capital owned by the village of Ciwaringin is quite good and runs as it functions. Keywords: Corporate Social Responsibility, Social Mapping, Community Empowerment